Role of Polarization in Halogen Bonds - Clark, Timothy; Murray, Jane S.; Politzer, Peter (Australian Journal of Chemistry, 2014)
A classical point-charge self-consistent polarization model has been used to investigate the role of polarization in the CF3Cl:OH2 complex. The polarised electron densities of the monomers component are shown to be a good representation of the electron densities of complexes, especially CF3Cl. The point-charge model overestimates the polarization of the water molecule, which is likely because exchange repulsion is unaccounted for in the classical model calculations.